Need Analysis for Developing Writing Skill Materials Using Facebook for English Undergraduate Students - Sakkir, Geminastiti; Dollah, Syarifuddin; Arsyad, Safnil; Ahmad, Jamaluddin (International Journal of Language Education, 2021)
This research is aiming at giving a contribution to the lecturers’ knowledge on the design materials in using social media Facebook in teaching writing process to English Department students. Before conducted the developing module for Facebook-based writing instructional course, we surveyed and explored the student’s need. The stages of this research consisted of need analysis and document analysis. We conducted needs analysis to 141 English students and 2 lecturers of writing. Data were collected using need analysis questionnaire and interview. The analyzed documents in this research were lesson plan, syllabus and the existing textbooks. The data from questionnaire and interview were analyzed in quantitative and qualitative methods. The results concluded that: first, needs analysis is the basic of developing module for Facebook-based writing instructional course, in order that the material can be related to the students’ needs, levels and lecturers’ perception. The result of students need found urgent to develop module for facebook-based writing instructional course through the following criteria of interactive, self-contained, user friendly, online supporting, online social media, authentic, environmentally friendly, formal and informal environments, online evaluation, presented in visual  aids, support  and facilitate the students’  academic and non-academic writing activities, topics of the materials should be interesting which provides a cultural background of students, the materials should be implemented by applying vocabulary, reading texts, grammar and basic skills in writing process, implemented in beginner level (Writing 1), used in class and out- class and the materials globally/ international context. Second, the lecturers’ desires in teaching writing are to improve the students’ skill to comprehend the materials. Third, the existing materials are unsuitable for the students, they prefer learning facilitated by electronic social media, Facebook, so they will more motivate in write.